Annual simulation, energy and economic analysis of hybrid heat pump systems for residential buildings. (25th April 2016) - Bagarella, G.; Lazzarin, R.; Noro, M.
Highlights: A model of a hybrid system (heat pump and condensing boiler) was implemented. Simulations were run with both a cold-humid and a mild-dry climate. With a large size HP, there are no benefits by setting a Tcut-off lower than BT . With a low size HP, a bivalent parallel system can lead to energy savings. Abstract: Air source heat pumps have a well known unfavourable characteristic: in the coldest period of the year, when the building heating load is at maximum, the heat pump capacity is reduced. A possible solution is to size the heat pump to cover only a fraction of the peak load using a second heat generator in "hybrid heat pump system". In this study, a dynamic model of a hybrid system was built, and several seasonal simulations were carried out (considering two different climates) to study how the choice of the cut off temperature can influence the annual efficiency of the system and to understand if a bivalent parallel plant can lead to energy savings compared to a bivalent alternative system. With both the considered climates, when a large size heat pump is selected (low bivalent temperature), there might be no benefits by setting a cut off temperature lower than the bivalent temperature, and the differences between the energy performances of the bivalent alternative system and those of the bivalent parallel system are negligible. On the other hand, when a low size heat pump is preferred (high bivalent temperature), the bivalent parallel system can lead to appreciable energy savings compared to a bivalent alternative plant. The main economic advantages of a hybrid system, with respect to the monovalent heat-pump plant, comes from the lower annual electric and gas energy needs.